Development of Licorice Flavonoids Loaded Microemulsion for Transdermal Delivery Using CCD-Optimal Experimental Approach: Formulation Development and Characterization - Xin, Yang; Yun, Shi; Yuhe, Lu; Yinxue, Mao; Shurui, Niu; Yue, Zhou; Kunming, Qin; Weidong, Li (Frontiers in Nanotechnology, 2021)
In this study, we sought to overcome the poor solubility and transdermal absorption rate of licorice flavonoids (LFs) by fabricating a LFs microemulsion. LFs content was determined using high performance liquid chromatography. Preliminary studies like solubility study, emulsification study and construction of the pseudo ternary phase diagram were performed for screening components, and optimized using a central composite design. Thirteen trial runs were executed by using two different variables, percent content of oil and the optimized ratio of emulsifier, and co-emulsifier whereas the responses investigated were solubility, droplet size and PDI. Microemulsions were then characterized for droplet size, PDI, transmission electron microscopy, viscosity, electrical conductivity, pH, entrapment efficiency, drug content and stability. Additionally, the release profile, percutaneous absorption, and skin retention were investigated using Franz diffusion cell. The optimal formulation was found to compose of laureth-9 (emulsifier, 6.72g), propylene glycol (co-emulsifier, 1.80g), isopropyl myristate (IPM, oil, 1.48g), LFs (1.50g) and at least more than 85% deionized water. The optimized and storage for three months microemulsion was found to clear, light yellow-colored with the absence of phase separation and precipitation denoted the stability of formulation to long-term placement. The mean droplet size, PDI, entrapment efficiency and drug content was observed as 12.68 ± 0.12 nm, 0.049 ± 0.005, 97.28 ± 0.13% and 122.67 ± 0.40 mg·g−1, respectively. Furthermore, the optimal formulation sustain released LFs, remarkedly deliver more LFs through the skin layer (644.95 ± 6.73μg·cm−²) and significantly retained LFs in the skin layer (9.98 μg·cm−²). The study concluded that optimized microemulsion has potential and enhanced the solubility and cumulative penetration amount of LFs.